Global proteomics and affinity mass spectrometry analysis of human Schwann cells indicates that variation in and loss of neurofibromin (NF1) alters protein expression and cellular and mitochondrial metabolism - Christian X Fay; Elizabeth R.M. Zunica; Elias Awad; William Bradley; Cameron Church; Jian Liu; Hui Liu; David K. Crossman; James A. Mobley; John P. Kirwan; Christopher L. Axelrod; Erik Westin; et al. (Scientific Reports)
Abstract In efforts to evaluate potential biomarkers and drug targets for Neurofibromatosis Type I (NF1) we utilized affinity mass spectrometry and global proteomics to investigate how variation within and loss of NF1 affect immortalized human Schwann cells. We used Strep tagged mNf1 cDNAs (both wild type (WT) and variant) to affinity purity NF1 Protein-Protein interactors (PPIs) from the Schwann cells. We were able to identify 98 PPIs and show that some of these PPIs bind differentially to variant proteins. Next, we evaluated global proteomes. We identified over 1900 proteins in immortalized human Schwann cells both with and without NF1 expression. We identified 148 proteins with differential expression levels based on genotype. Following Ingenuity Pathway analysis (IPA) we found multiple pathways were altered including decreases in “oxidative phosphorylation,” increases in “mitochondrial dysfunction”, and “glycolysis”, as well as changes in “Myelination Signaling Pathway.” When we evaluated the proteome of NF1 null cells stably transfected with tagged mNf1 cDNAs we again identified an overall trend of metabolic differences pertaining to “oxidative phosphorylation”, “mitochondria dysfunction”, and “glycolysis” in the variant cDNA expressing cells. We then validated differential expression of the following proteins: LAMC1, CYB5R3, and SOD2 that are observed in the altered pathways. Finally, consistent with our proteomics findings, we show that NF1 is required to maintain mitochondrial respiratory function in Schwann cells by stabilizing NADH-linked oxidative phosphorylation and electron transfer. Taken together, these data indicate that NF1 plays a significant role in mitochondrial metabolism that results in proteomic changes in Schwann cells and may serve as a future drug target.